Hubungan Kedisiplinan Dengan Motivasi Belajar Siswa Kelas IV SDN 106170 Ajibaho 2020/2021 - Rianita Br Barus; Nizmi Putri (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2022)
The formulation of the problem in this study is the low level of student motivation due to the low level of student discipline. This study aims to determine how big the level of relationship between student discipline and learning motivation of fourth grade students at SDN 106170 AJIBAHO for the 2020/2021 Academic Year. This research is a correlational study with the number of research subjects as many as 76 students from fourth grade students at SDN 106170 AJIBAHO for the 2020/2021 Academic Year. This research was carried out in two stages, the first stage was a questionnaire trial, then the second stage was the distribution of the questionnaire to all samples of class IV SDN 106170 AJIBAHO for the 2020/2021 academic year. There are two variables in this study, student discipline as the independent variable and student motivation as the dependent variable. Data collection techniques in this study used a questionnaire. The data analysis technique used is the Product Moment Correlation analysis formula, determination and t test. From the calculation results, the level of tendency of the variable x (student discipline) is included in the category of tending to be moderate. While the level of tendency of the variable y (student learning motivation) is included in the category tend to be too. The results of the t-test calculation show that tcount = 8.85 while ttable = 1.99 with dk = n-2 at a significant level of alpha = 0.05, thus the hypothesis that states "there is a relationship between student discipline and student learning motivation in students grade IV SDN 106170 AJIBAHO Academic Year 2020/2021” has been verified (Ha is accepted and significant because tcount > ttable